Aplicação da teoria dos grafos no ensino médio à luz das contribuições do PROFMAT - Souza, Marcelo Silva de (2016)
This paper presents an inclusive proposition of the theme routes, in the graph theory, in high school. Initially, we identified some renovations in the last years, in legal and curricular aspects of Brazilian education that allow, even in an introductory way, the insertion of the Graph Theory in Basic Education, as such reforms direct to contextualization, modeling, solving problems, among other natural aspects of the theory. These characteristics can be verified in the following two chapters, through its main problems, and through PROFMAT dissertations analysis. Finally, we present a proposal directed to high school students that was built through the introductory concepts of graph theory necessary to understand the ideas of routes and critical path and concludes with the presentation of Dijkstra Algorithm, Method exhaustion and Greedy Algorithm.